Blood samples collected under anesthesia can be used as a source of non-diseased controls for immune-based assays - Domingo-Vila, Clara; Williams, Evangelia D.; Smithmyer, Megan E.; Benson, Basilin; Ferrat, Lauric A.; Arif, Sefina; Hudson, Michelle; Dobbs, Becky; Johnson, Matthew B.; Yardley, Iain; Speake, Cate; Oram, Richard A.; et al. (Frontiers in Immunology, 2025)
Recruiting very young, healthy children to serve as age-matched controls in research presents substantial ethical and practical challenges. One potential approach to address this issue is to recruit healthy children who are referred for elective procedures under general anesthesia. As infants are typically anesthetized using volatile anesthetics before cannula insertion for additional drug administration, blood samples become readily accessible after the onset of drug-induced coma. However, since prolonged exposure to inhaled anesthetic agents is known to have immune-modulating effects that could affect their suitability as experimental controls, we aimed to investigate whether immune changes are also present in samples collected immediately after gas induction in children undergoing elective dental procedures. The composition and transcriptional profile of whole blood immune cells were assessed using multiparameter flow cytometry and bulk RNA-sequencing, respectively. Cryopreserved PBMCs were used to study changes in the phenotype of polyclonally activated CD4+ T cells by single-cell RNA sequencing using the 10x Genomics (Pleasanton, CA, USA) platform. We report that inhaled anesthetic induction with a combination of nitrous oxide and sevoflurane has minimal effect on immune system composition and transcriptional profiles, and does not alter the phenotype of CD4+ T cells activated with staphylococcal enterotoxin B (SEB). However, we observed increased absolute cell counts in specific leucocyte populations. We conclude that blood samples collected during elective procedures under general anesthesia may represent a valuable opportunity for recruiting healthy children for research studies, depending on the intended assays.